PENINGKATAN PERAN KADER KESEHATAN REMAJA TERHADAP PEMELIHARAAN KESEHATAN DI SEKOLAH MENENGAH ATAS - Anggraeny, Dyta; Datunsolang, Vanessa; Nurwidyah; Raudina Hudani Amali; Pratiwi Cahya Lamante; Nadiathul Pontoh; Sri Wahyu Ningsih (P3M Universitas Aisyiyah Surakarta, 2024)
Community service in tertiary institutions with the subject being carried out by students in the form of Kuliah Kerja Nyata (KKN). The essence of the implementation of these activities is that the knowledge that has been obtained in the previous semester is applied to certain communities. The implementation of this community service was at SMA Negeri 1 Kotamobagu with the target subject of the activity being Kader Kesehatan Remaja (KKR). Adolescence is a period where there is potential to implement Germas because of today's socialization which uses digital technology more often so that it is more effective and efficient to disseminate information besides that the adolescent stage which becomes decisive in adulthood is to be able to adopt a good lifestyle by minimizing the number of cases or health problems became the reason for determining the KKR as the target of community service activities. After the analysis of the matrix criteria technique, there are 4 priority problems to be intervened, namely smoking, minimal reproductive health awareness, ignorance of the description of Basic Life Support (BLS) provision and lack of knowledge about drug consumption. Of the four priority issues, there are 5 activities that will be carried out as community service, namely education on the dangers of smoking, education on menstruation hygiene management, education on drug classification, simulation of breast self-examination, simulation of checking vital signs, simulation of giving BLS. The results showed that any knowledge in the high category experienced an increase after being given education. In addition, the simulation given based on the scoring carried out by the community service team for students who did repetition of the demonstration after the simulation was quite good. Therefore, it is hoped that the success of the activities carried out by the community service team this time, community service can pass on the information obtained to all school parties. Keywords: education; simulation; health; youth